The relationship between autophagy and the immune system and its applications for tumor immunotherapy - Jiang, Guan-Min; Tan, Yuan; Wang, Hao; Peng, Liang; Chen, Hong-Tao; Meng, Xiao-Jun; Li, Ling-Ling; Liu, Yan; Li, Wen-Fang; Shan, Hong (Molecular cancer, 2019)
Autophagy is a genetically well-controlled cellular process that is tightly controlled by a set of core genes, including the family of autophagy-related genes (ATG). Autophagy is a "double-edged sword" in tumors. It can promote or suppress tumor development, which depends on the cell and tissue types and the stages of tumor. At present, tumor immunotherapy is a promising treatment strategy against tumors. Recent studies have shown that autophagy significantly controls immune responses by modulating the functions of immune cells and the production of cytokines. Conversely, some cytokines and immune cells have a great effect on the function of autophagy. Therapies aiming at autophagy to enhance the immune responses and anti-tumor effects of immunotherapy have become the prospective strategy, with enhanced antigen presentation and higher sensitivity to CTLs. However, the induction of autophagy may also benefit tumor cells escape from immune surveillance and result in intrinsic resistance against anti-tumor immunotherapy. Increasing studies have proven the optimal use of either ATG inducers or inhibitors can restrain tumor growth and progression by enhancing anti-tumor immune responses and overcoming the anti-tumor immune resistance in combination with several immunotherapeutic strategies, indicating that induction or inhibition of autophagy might show us a prospective therapeutic strategy when combined with immunotherapy. In this article, the possible mechanisms of autophagy regulating immune system, and the potential applications of autophagy in tumor immunotherapy will be discussed.